C9orf72-Associated Dipeptide Repeat Expansions Perturb ER-Golgi Vesicular Trafficking, Inducing Golgi Fragmentation and ER Stress, in ALS/FTD - Jessica Sultana; Audrey M. G. Ragagnin; Sonam Parakh; Sayanthooran Saravanabavan; Kai Ying Soo; Marta Vidal; Cyril Jones Jagaraj; Kunjie Ding; Sharlynn Wu; Sina Shadfar; Emily K. Don; Anand Deva; et al. (Molecular Neurobiology, 2024)
Hexanucleotide repeat expansions (HREs) in the chromosome 9 open reading frame 72 ( C9orf72 ) gene are the most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Both are debilitating neurodegenerative conditions affecting either motor neurons (ALS) in the brain and spinal cord or neurons in the frontal and/or temporal cortical lobes (FTD). HREs undergo repeat-associated non-ATG (RAN) translation on both sense and anti-sense strands, generating five distinct dipeptide repeat proteins (DPRs), poly-GA, -GR, -GP, -PA and -PR. Perturbed proteostasis is well-recognised in ALS pathogenesis, including processes affecting the endoplasmic reticulum (ER) and Golgi compartments. However, these mechanisms have not been well characterised for C9orf72-mediated ALS/FTD. In this study we demonstrate that C9orf72 DPRs polyGA, polyGR and polyGP (× 40 repeats) disrupt secretory protein transport from the ER to the Golgi apparatus in neuronal cells. Consistent with this finding, these DPRs also induce fragmentation of the Golgi apparatus, activate ER stress, and inhibit the formation of the omegasome, the precursor of the autophagosome that originates from ER membranes. We also demonstrate Golgi fragmentation in cells undergoing RAN translation that express polyGP. Furthermore, dysregulated ER-Golgi transport was confirmed in C9orf72 patient dermal fibroblasts. Evidence of aberrant ER-derived vesicles in spinal cord motor neurons from C9orf72 ALS patients compared to controls was also obtained. These data thus confirm that ER proteostasis and ER-Golgi transport is perturbed in C9orf72-ALS in the absence of protein over-expression. Hence this study identifies novel molecular mechanisms associated with the ER and Golgi compartments induced by the C9orf72 HRE.